Pembelajaran Berkarakteristik Inovatif Abad 21 pada Materi K3lh dengan Model Pembelajaran Ceramah di Sekolah SMK Negeri 1 Dukuhturi - Nugroho, Sigit (Universitas Pancasakti Tegal, 2022)
The use of clear strategies in learning can provide direction during the learning process so that the learning objectives that have been set can be achieved optimally and the learning process can take place effectively and efficiently. Learning strategies are not only useful for teachers but also for students. For teachers, learning strategies can be used as guidelines and references for systematic action in the implementation of learning. For students, the use of learning strategies can facilitate the learning process in understanding the content of learning, because each learning strategy is designed to facilitate the students' learning process. In improving learning outcomes and student learning experiences, teachers need to develop learning strategies that are tailored to the material and conditions of students.